A QoS oriented vertical handoff scheme for WiMAX/WLAN overlay networks - Ma, Dong (2013)
Recently, a number of wireless communication technologies are migrating toward heterogeneous overlay networks. The integration of Mobile WiMAX and WLAN seems to be a promising approach due to their homogeneous nature and complementary characteristics. In this paper, we investigate several important issues for the interworking of Mobile WiMAX and WLAN networks. We address a tightly coupled interworking architecture. Further, a seamless and proactive vertical handoff scheme is designed based on the architecture with aims to provide always the best quality of service (QoS) for users. Both the performance of applications and network conditions are considered in the handoff process. Moreover, we derive evaluation algorithms to estimate the conditions of both WiMAX and WLAN networks in terms of available bandwidth and packet delay. A simulation study has demonstrated that the proposed schemes can keep stations always being best connected.